Petrografia e geoquímica da ocorrência de (clinopiroxênio)-hastingsita-biotita-granada ortognaisse na região de Santa Cruz do Prata - MG - Leme, Thaís Guitzlaf [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In the region of Santa Cruz do Prata, southwest of Minas Gerais, the occurrence of (clinopyroxene)-hastingsite-biotite-garnet orthogneiss was recorded between rocks attributed to the Araxá Group, close to the tectonic contact with lithotypes attributed to the Guaxupé Complex. The mineral assemblage present in the orthogneiss is uncommon, and not completely described and understood in the region. In this work are presented petrographic, geochemical, of mineral chemistry, thermobarometric and isotopic data with the purpose of characterizing the occurrence of this lithotype. This rock has structures that varies from isotropic to anisotropic, and may show much more foliated and oriented domains, due to the greater degree of deformation. In the less deformed portions it is possible to identify preserved primary igneous features. The mineralogical, textural, and petrological aspects suggest that the orthogneiss protolith was a granitic rock composed of orthoclase, plagioclase, garnet, clinopyroxene and quartz, originated under conditions of minimum temperatures of 900 °C, and pressures above 15 Kbar. The lithogeochemical analyzes show that the orthogneiss presents a calcic-alkaline chemical composition, with metaluminous to peraluminous character, classified as granodiorite to granite, with compositional characteristics similar to that of rocks generated in magmatic arcs. The obtained data indicate metamorphic peak under granulite facies conditions, with minimum temperatures of 800 °C and pressures higher than 12.5 kbar, and retrometamorphic re-equilibrium under conditions of 670 °C to 750 °C and 10.0 kbar to 12.5 Kbar in medium to high amphibolite facies, with metamorphic trajectory clockwise, compatible with continental collision zones

Na região de Santa Cruz do Prata, sudoeste de Minas Gerais, foi registrada a ocorrência de (clinopiroxênio)-hastingsita-biotita-granada ortognaisse encaixado em rochas atribuídas ao Grupo Araxá, próximo ao contato tectônico com litotipos atribuídos ao Complexo Guaxupé. A associação mineral presente no ortognaisse é incomum, e não completamente descrita e compreendida na região. Neste trabalho são apresentados dados petrográficos, geoquímicos, de química mineral, termobarométricos e isotópicos com a finalidade de caracterizar a ocorrência do litotipo. Esta rocha apresenta estrutura que varia de isotrópica a anisotrópica, podendo exibir domínios bem mais foliados e orientados, em consequência do maior grau de deformação. Nas porções menos deformadas é possível identificar feições ígneas primárias preservadas. Os aspectos mineralógicos, texturais e petrológicos sugerem que o protólito do ortognaisse seria uma rocha granítica composta por ortoclásio, plagioclásio, granada, clinopiroxênio e quartzo, originada em condições de temperaturas mínimas da ordem 900 °C, e pressões acima de 15 kbar. As análises litogeoquímicas mostram que o ortognaisse apresenta composição química cálcica-alcalina, com caráter metaluminoso a peraluminoso, classificado como granodiorito a granito, com características composicionais semelhantes à de rochas geradas em arcos magmáticos. Os dados obtidos indicam ápice metamórfico em condições de fácies granulito, com temperaturas mínimas de 800 °C e pressões superiores a 12,5 kbar, e reequilíbrio retrometamórfico em condições de 670 °C a 750 °C e 10,0 kbar a 12,5 kbar em fácies anfibolito médio a alto, com trajetória metamórfica em sentido horário, compatível com zonas de colisão continental
Keywords: Petrologia; Geoquimica; Cisalhamento dos solos; Minas Gerais